Diseño de un modelo a escala laboratorio de un sistema de levantamiento artificial con bomba PCP (2019)
Initially, a description was made of the generalities of the PCP system, its advantages and disadvantages, equipment used in bottom and surface and their installation, manufacturers of PCP pumps, and other important factors of the system. Subsequently, the faults present in the PCP pumps were identified and described. causes and recommended actions to be taken when these occur in the system. This was followed by the well design with the help of the AutoCad 2016 drawing program, which was based on three main components, type of rock store which will act as a producer formation, type of rock seal and type of fluid stored. The PCP system was also designed to scale in the drawing program AutoCad 2016 based on the characteristics of the pump supplied by the company NETZSCH, which has the name NM008*3S.